Adalbero of Laon's Poem to King Robert (1023–1025/7): a discourse against Cluniac reform or a commentary on monastic hypocrisy? - Vanderputten, Steven (Early Medieval Europe, 2024)
The purpose of this paper is to nuance the traditional interpretation of Bishop Adalbero of Laon's satirical Carmen ad Rotbertum regem as a rebuttal of Cluniac reform and its disruptive effect on early eleventh‐century society. Study of the text's literary antecedents reveals that its criticism was rooted in a tradition of commentaries on the conduct and attitudes of a much larger monastic cohort. Furthermore, comparison of its argument with evidence about the context and with a number of polemical statements regarding the relations between bishops and monastic leaders since the 990s indicates that the author's focus was on cautioning against abbots' hypocrisy rather than against a programmatic reform.